Does oil substitute for patriarchy?. (23rd December 2018) - Simmons, Joel W.
Abstract: Critics of Ross's (American Political Science Review, 102, 2008, 107) gendered resource curse thesis argue that culture trumps oil wealth as a determinant of female labor force participation (FLFP). Here, I argue that, while cultural attributes do indeed affect the female labor supply, oil wealth reduces the demand for female labor by hurting the export‐oriented industries that employ female labor intensively. By reducing the demand for female labor in this way, oil wealth undermines the positive effect of gender egalitarianism on FLFP. Thus, oil curses women. Using data from the World Values Survey and the World Bank, I find support for the argument.